Smoking, Discount Rates, and Returns to Education - Josef Fersterer; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2000)
Individual time preference determines schooling enrolment. Moreover, smoking behavior in early ages has been shown to be highly related to time preference rates. Accordingly, we use smoking at age 16 as an instrument for schooling in order to cope with ability bias in a returns to education regression. Doing this for Austrian cross-sectional data, we find no evidence of ability bias.
Keywords: I22; J31; 330; Returns to education; instrumental variables; ability bias; discount rates; Bildungsertrag; Rauchen; Soziale Diskontrate; Österreich